Frequency of Euthyroid Sick Syndrome before and after renal transplantation in patients with end stage renal disease and its association with oxidative stress. Issue 1 (2nd January 2022) - Akman, Tugce; Topaloglu, Oya; Altunoglu, Alparslan; Neselioglu, Salim; Erel, Ozcan
ABSTRACT: Objective: In this study, we aimed to evaluate the frequency of euthyroid sick syndrome (ESS) before and after renal transplantation in patients with end-stage renal disease (ESRD), and its association with oxidative stress (OS) by evaluating thiol-disulfide levels. Methods: Free triiodothyronine (fT3), free thyroxine (fT4) thyroid stimulating hormone (TSH), and thiol and disulfide levels were recorded before and after renal transplantation in patients with ESRD. ESS was diagnosed in patients with unresponsive TSH to low fT3 and/or fT4 levels. Results: A total of 121 patients were included in the study. Of these, 69 (57%) were males and 52 (43%) were females. The mean age was 45 ± 12.61 years. ESS was detected in 39 (32%) of 121 patients. Of 39 patients, 24 (61%) had ESS before transplantation and 15 (39%) after transplantation. Sixteen of 24 (66.7%) patients with ESS before transplantation reached normal thyroid functions after transplantation. In post transplantation period, patients with ESS had significantly higher urea and creatinine (p = 0.025 and p = 0.009, respectively) compared to patients without ESS. Furthermore, thiol-disulfide levels of 20 patients with ESS at any time compared with 68 patients without ESS. It was found that native thiol and total thiol were significantly lower in patients with ESS (p = 0.025 and p = 0.044, respectively). Conclusion: The present study is an initial evaluation of the OS and antioxidant status in the etiology of ESS in patients with renal transplantation. These patients have markedly low levels of antioxidant products, which support the possible role of OS in ESS.